Cardinal Buoys: An Opportunity for the Study of Air-Sea CO2 Fluxes in Coastal Ecosystems - Gac, Jean-Philippe; Marrec, Pierre; Cariou, Thierry; Guillerm, Christophe; Macé, Éric; Vernet, Marc; Bozec, Yann (Frontiers in Marine Science, 2020)
From 2015 to 2019 we installed high-frequency (HF) sea surface temperature, salinity, fluorescence, dissolved oxygen and partial pressure of CO2 (pCO2) sensors on a cardinal buoy of opportunity (ASTAN) at a coastal site in the southern Western English Channel (sWEC) highly influenced by tidal cycles. The sensors were calibrated against bimonthly discrete measurements performed at two long-term time series stations near the buoy, thus providing a robust multi-annual HF dataset. The tidal transport of a previously unidentified coastal water mass and an offshore water mass strongly impacted the daily and seasonal variability of pCO2 and pH. The maximum tidal variability associated to spring tides (> 7m) during phytoplankton blooms represented up to 40% of the pCO2 annual signal at ASTAN. At the same time, the daily variability of 0.12 pH units associated to this tidal transport was 6 times larger than the annual acidification trend observed in the area. A frequency/time analysis of the HF signal revealed the presence of a day/night cycle in the tidal signal. The diel biological cycle accounted for 9% of the annual pCO2 amplitude during spring phytoplankton blooms. The duration and intensity of the biologically productive periods, characterized by large inter-annual variability, were the main drivers of pCO2 dynamics. HF monitoring enabled us to accurately constrain, for the first-time, annual estimates of air-sea CO2 exchanges in the nearshore tidally-influenced waters of the sWEC, which were a weak source to the atmosphere at 0.51 mol CO2 m-2 yr-1. This estimate, combined with previous studies, provided a full latitudinal representation of the WEC (from 48°75’N to 50°25’N) over multiple years for air-sea CO2 fluxes in contrasted coastal ecosystems. The latitudinal comparison showed a clear gradient from a weak source of CO2 in the tidal mixing region towards sinks of CO2 in the stratified region with a seasonal thermal front separating these hydrographical provinces. In view of the fact that several continental shelf regions have been reported to have switched from sources to sinks of CO2 in the last century, weak CO2 sources in such tidal mixing areas could potentially become sinks of atmospheric CO2 in coming decades.